2019
DOI: 10.4103/ija.ija_25_19
|View full text |Cite
|
Sign up to set email alerts
|

A new indication of erector spinae plane block for perioperative analgesia is total hip replacement surgery – A case report

Abstract: A new indication of ultrasound – guided Erector spinae plane block for perioperative analgesia is orthopaedic surgery. We report here the use of this paraspinal block in the case of a 68-yr-old female with multiple systemic disorder for total hip replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…is is one of the few randomized controlled trials to evaluate the use of lumbar ESPB for analgesia in total hip arthroplasty. In terms of efficacy, our results are consistent with recent case reports and observational studies of ESPB utilized in hip surgeries, only one of which pertains specifically to total hip arthroplasties [5][6][7][8][9]. e most similar study was performed by Ahiskalioglu et al, who demonstrated that deposition of 40 ml of a local anesthetic mixture (20 ml 0.5% bupivacaine, 10 ml lidocaine 2%, and 10 ml normal saline) between the erector spinae and L4 transverse process for both hemiarthroplasties and intramedullary femur nailing resulted in adequate analgesia with a median time of 8 hours [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…is is one of the few randomized controlled trials to evaluate the use of lumbar ESPB for analgesia in total hip arthroplasty. In terms of efficacy, our results are consistent with recent case reports and observational studies of ESPB utilized in hip surgeries, only one of which pertains specifically to total hip arthroplasties [5][6][7][8][9]. e most similar study was performed by Ahiskalioglu et al, who demonstrated that deposition of 40 ml of a local anesthetic mixture (20 ml 0.5% bupivacaine, 10 ml lidocaine 2%, and 10 ml normal saline) between the erector spinae and L4 transverse process for both hemiarthroplasties and intramedullary femur nailing resulted in adequate analgesia with a median time of 8 hours [8].…”
Section: Discussionsupporting
confidence: 90%
“…Since then, there have been studies demonstrating its efficacy with a thoracic approach for analgesia in breast surgery and rib fractures [4]. Only a few case reports to date have demonstrated a lumbar approach to achieve analgesia for hip arthroplasty [5][6][7]. Two major benefits to this block are its relatively low risk of complications due to its anatomical position [5], as well as the lack of risk of mechanical nerve damage as there is no direct contact with any nerves [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, other authors have also published case reports of lumbar ESPB for THA with favourable outcomes [26,27]. Continuous ESPB catheters have also been used for postoperative analgesia in THA [28,29]. In 2020, Ahiskalioglu et al conducted an observational study on fifteen high risk elderly patients undergoing hip surgery and demonstrated that lumbar ESPB when combined with mild propofol sedation provides adequate and safe anaesthesia for hip surgery.…”
Section: Newer Regional Anaesthesia Techniques (Table-5) a Supraingui...mentioning
confidence: 99%
“…Lumbar ESPB was first described for hip surgery 8 and later for use in hip and femur surgery. 17,24,25,29,39,[64][65][66][67][68] Radiological evaluation and clinical results have shown that high volume lumbar ESPB results in similar analgesia as lumbar plexus block. 29,32 It has also been reported for the postoperative analgesia of knee surgery.…”
Section: Orthopedic Proceduresmentioning
confidence: 99%